Distinct hyperpolarizing and relaxant roles for gap junctions and endothelium-derived H(2)O(2) in NO-independent relaxations of rabbit arteries - Chaytor, Andrew T. (National Academy of Sciences, 2003)
We have compared the contributions of gap junctional communication and chemical signaling via H(2)O(2) to NO-independent relaxations evoked by the Ca(2+) ionophore A23187 and acetylcholine (ACh) in rabbit ilio-femoral arteries. Immunostaining confirmed the presence of connexins (Cxs) 37 and 40 in the endothelium and Cxs 40 and 43 in smooth muscle. Maximal endothelium-dependent subintimal smooth muscle hyperpolarizations evoked by A23187 and ACh were equivalent (≈20 mV) and almost abolished by an inhibitory peptide combination targeted against Cxs 37, 40, and 43. However, maximal NO-independent relaxations evoked by A23187 were unaffected by such peptides, whereas those evoked by ACh were depressed by ≈70%. By contrast, the enzyme catalase, which destroys H(2)O(2), attenuated A23187-induced relaxations over a broad range of concentrations, but only minimally depressed the maximum response to ACh. Catalase did not affect A23187- or ACh-evoked hyperpolarizations. After loading with an H(2)O(2)-sensitive probe, A23187 caused a marked increase in endothelial fluorescence that correlated temporally with relaxation, whereas only a weak delayed increase was observed with ACh. In arteries without endothelium, the H(2)O(2)-generating system xanthine/xanthine oxidase induced a catalase-sensitive relaxation that mimicked the gap junction-independent response to A23187 as it was maximally equivalent to ≈80% of induced tone, but associated with a smooth muscle hyperpolarization <5 mV. We conclude that myoendothelial gap junctions underpin smooth muscle hyperpolarizations evoked by A23187 and ACh, but that A23187-induced relaxation is dominated by extracellular release of H(2)O(2). Endothelium-derived H(2)O(2) may thus be regarded as a relaxing factor, but not a hyperpolarizing factor, in rabbit arteries.